Humoral responses to the SARS-CoV-2 spike and receptor binding domain in context of pre-existing immunity confer broad sarbecovirus neutralization - Hauser, Blake M.; Sangesland, Maya; Lam, Evan C.; Feldman, Jared; Balazs, Alejandro B.; Lingwood, Daniel; Schmidt, Aaron G. (Frontiers in Immunology, 2022)
Since the emergence of SARS-CoV-2 (SARS-2), multiple vaccine candidates were developed and studied both preclinically and clinically. Nearly all are based on the SARS-2 spike glycoprotein or its receptor binding domain (RBD). Studies of these vaccine candidates have largely been in a SARS-2 naïve context. However, pre-existing immunity to SARS-2 acquired through infection or vaccination continues to increase. Evaluating future vaccine candidates in context of this pre-existing immunity is necessary to understand how immune responses are subsequently influenced. Here, we evaluated the serum and IgG+ B cell responses to the SARS-2 RBD in context of pre-existing immunity elicited by the full SARS-2 spike, and we compared this to boosting with the full SARS-2 spike. Boosting with the SARS-2 RBD resulted in increased reactivity to RBD epitopes, but both immunization regimens resulted in similarly broad neutralization across diverse sarbecoviruses. These findings may inform comparison among SARS-2 RBD-based vaccine candidates to currently approved spike-based candidates.